Design of Garbage Disposal Flow on Jalan Petir Tasikmalaya - Isma Nurul Aini; Meita Annisa Nurhutami (Journal of Industrial Product Design Research and Studies, 2022)
The problem of waste in Indonesia is an endless topic to talk about. Various methods have been carried out as an effort to overcome the overflowing pile of garbage, especially the garbage that is scattered everywhere, including in the ditches. This problem can spread to all aspects of life such as health, social, environmental, economic, even political and cultural. The lack of public understanding of environmental conservation and the poor quality of waste management are the main factors in the accumulation of waste that occurs in Indonesia, especially in densely populated areas. This study aims to find an approach related to waste reduction and management solutions on Jalan Petir, Tawang District, Tasikmalaya City so that it does not scatter and clog the surrounding waters, especially the ditches that stretch along densely populated roads. This research using survey methods and qualitative analysis has resulted in the design of a coordinated waste disposal flow from households, the process of sorting waste to temporary shelters and ending in final disposal sites that cannot be separated from cooperation between the community, the government, and surrounding businesses. It is very important to do this so that the process and goal of reducing waste accumulation runs well and reduces the risk of other adverse impacts such as floods, virus outbreaks, and other disasters that can occur if this waste problem is not handled properly as it should be.